Implementasi Konsep "BETAH" dalam Pelaksanaan Ujian Akademik Penerimaan Polri Terpadu Polda Sumatera Utara berbasis Komputer dan Manual - Limbong, Tonni; Suardana, I.K (MEANS (Media Informasi Analisa dan Sistem), 2018)
The current examination must be clean and honest in order to get good and integrity resources so that the institutions that carry out the reception of human resources will be satisfied and successful. Likewise in the current era of computerization the North Sumatra regional police in carrying out personnel recruitment applies the concept of "TRUE" which means "Clean Transparent Accountable and Humanistic" with the jargon of Clear and Clean. Examination of the Academic Exams in accordance with the instructions and instructions from the National Police Headquarters of the Republic of Indonesia is carried out by combining computer technology with conventional models / manuals with Computer Answer Sheets (LJK). All selection participants who passed and did not pass were satisfied because with this method each participant could see the selection process from beginning to end in a very transparent manner, so that the perception of the community had always been negative thinking that the national police selection was not free from KKN practices. The concept of CONCRETE is a very good method and can be accounted for by all the elements involved in the process and can realize the selection process that is "Clear and Clean"